The high frequency component of the vertical ground reaction force is a valid surrogate measure of the impact peak. Issue 3 (8th February 2016) - Blackmore, Tim; Willy, Richard W.; Creaby, Mark W.
Abstract: Identification of the impact peak (IP) from the vertical ground reaction force (vGRF) is required to calculate indices of impact loading during running. The IP, however, is not always clearly discernible. Previous researchers have estimated the timing of the IP using surrogate methods, the most common of which is a set time point of 13% stance (TPS). Information contained within the high frequency (HiF) component of the vGRF may also have a utility as a surrogate measure, but the validity of either approach is currently unknown. The purpose of this study is to evaluate the criterion validity for a newly proposed HiF method and the previously used TPS method against a criterion measure for a group of rear-foot striking runners. Fifty participants ran at a standardized speed (3.3 m·s −1 ) on an instrumented treadmill. Five consecutive stance phases were analyzed for the participant's dominant limb. Bland–Altman was used to assess agreement between the criterion method and each surrogate method. Good agreement of the HiF and TPS methods with the criterion method indicate that both methods are likely to be valid surrogate approaches to estimate vGRF impact loading indices. For all impact loading indices, smaller bias and limits of agreement (LOA) were observed with the HiF method when compared to the TPS method. Therefore, it is concluded that the HiF method should be used in preference to the TPS method when it is available.